Recombinant Human Thyroid-Stimulating Hormone Increases the Percentages of Natural Killer T Cells and B Lymphocytes in Human Peripheral Blood In Vivo - Adamczewski, Zbigniew; Stasiołek, Mariusz; Zygmunt, Arkadiusz; Śliwka, Przemysław W.; Wieczorek-Szukała, Katarzyna; Lewiński, Andrzej (Frontiers in Endocrinology, 2020)
Multiple cellular and humoral components of immune system play a significant role in the physiology and pathophysiology of various organs including the thyroid. On the other hand, both thyroid hormones and TSH have been shown to exert immunoregulatory activities, which are difficult to assess independently in vivo. In our study we employed a unique clinical model for the assessment of TSH biological function in humans. The structure of peripheral blood mononuclear cell populations was investigated, using flow cytometry, in athyroid patients (n=109) after treatment because of the differentiated thyroid carcinoma (DTC) at two time-points: directly before and five days after recombinant human TSH (rhTSH) administration. The analysis revealed significant increase in the percentage of natural killer T cells and B lymphocytes in the peripheral blood of rhTSH treated patients. Whereas, we did not observe any effects on investigated subpopulations of dendritic cells and monocytes, T cells and natural killer cells. The findings of the study indicate immune regulatory role of TSH, directed specifically on selected cell subtypes.